Saving Derawan Island from Abration for Marine Tourism Suistainable - Dadang Ilham Kurniawan Mujiono; Nurfitriana Pereda Prahara; Kurnianto Rambe Rante; Bella Arisandy (Jurnal Segara, 2020)
As an archipelago state, Indonesia globally famous with mega marine biodiversity. This country contributes the most extensive area among six countries under the Coral Triangle area. The area contains almost 600 species of corals and, 76% of total corals worldwide found in the coral triangle. Moreover, 574 of coral species which 72% of total corals globally located in Indonesia, and Raja Ampat hosting the highest biodiversity followed by Derawan Island in East Kalimantan Province. Despite having extraordinary marine biodiversity, Derawan Island experience several environmental issues. One of them is Abrasion. Data collecting are through observation and in-depth interview. The research shows that Derawan Island experienced massive abrasion on the East side of the island due to  housing developments in the South area of the island. As the consequences, the water current which carried the sand from the East and the Westside was stuck in the South area of the island. Therefore, the solutions that can be conducted are: (1) building erosion prevention; (2) coral reef treatment; (3) relocation for people who live on the coastline.